Malaria parasitemia and its association with lipid and hematological parameters among malaria-infected patients attending at Metema Hospital, Northwest Ethiopia - Sirak S; Fola AA; Worku L; Biadgo B (Dove Medical Press, 2016)
Solomon Sirak,1,* Abebe Alemu Fola,2 Ligabaw Worku,3 Belete Biadgo4,* 1Department of Medical Laboratory Sciences, College of Medicine and Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 2Walter and Eliza Hall Institute of Medical Research, Melbourne, VIC, Australia; 3Department of Medical Parasitology, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 4Department of Clinical Chemistry, School of Biomedical and Laboratory Sciences, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia *These authors contributed equally to this work Background: Malaria is a major public health problem in Ethiopia with wide-ranging hematological and biochemical alterations. Therefore, the aim of this study was to assess malaria parasitemia and its association with lipid and hematological parameters. Methods: A comparative cross-sectional study was conducted from April 1 to June 30, 2014. Of 200 study participants, 100 were confirmed malaria patients and 100 healthy controls. Study participants were included based on systematic random sampling techniques. Seven milliliters of blood samples were collected for investigation of hematological and lipid parameters. Data were entered and analyzed using SPSS-20 statistical software. Independent t-test and one-way analysis of variance were run to compare mean differences. A P<0.05 was considered as statistically significant. Results: A total of 200 study participants (78.5% males and 21.5% females) were included with a mean age of 24.67±11.2 years. A majority of malaria patients were infected with Plasmodium falciparum (66%). According to parasitic load, 38%, 52%, and 10% patients were reported with low, moderate, and high malaria parasitemia, respectively. There were statistically significant mean differences in white blood cells count ([6.875±3.20 vs 5.835±2.01]×103/µL), neutrophil (63.1%±8.7% vs 56.0%±12.7%), hemoglobin (11.9±2.0 vs 14.5±3.0 gm/dL), hematocrit (36.2%±7.8% vs 42.4%±8.3%), platelet count ([175.3±136 vs 193.4±81.9]×103/µL), high-density lipoprotein (19.6±13.7 vs 35.5±12.3 mg/dL), low-density lipoprotein (34.7±23.5 vs 64.5±29.3 mg/dL), triglyceride (118.0±61.3 vs 101.7±36.8 mg/dL), and total cholesterol (88.0±36.3 vs 148.7±39.1 mg/dL) for cases and controls, respectively (P<0.05). In patients with different densities of malaria parasitemia there were statistically significant differences in total red blood cells count ([4.4±0.8 vs 4.8±0.8 vs 5.3±0.7] ×106/µL), hemoglobin concentration ([11.9±1.8 vs 11.6±1.8 vs 13.4±3.0] gm/dl), and platelet count ([227.1±131 vs 186.8±175 vs 156.9±100] ×103/uL) among low, moderate, and high parasitemia, respectively. Conclusion: This study revealed that routinely used laboratory tests such as lipid and hematological parameters could be good and reliable adjunct in the early diagnosis of malaria-infected patients with mild-to-severe parasitemia in malaria endemic areas. Keywords: malaria parasitemia, hematological parameters, lipid parameters, Ethiopia